EFFECT OF TEA TREE (MELALEUCA ALTERNIFOLIA) GEL ON FIBROBLASTS, BLOOD VESSELS AND COLLAGEN POST-EXODONTICS - Runting, Nina; Hernanti, Degi Intan; Bintara Putra, Dimas Bagus Prayogi; Puteri, Sabila Intania (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Dental exodontics cause wounds to the surrounding tissue where the exodontic procedure was performed. The wound healing process is influenced by the formation of new blood vessels, fibroblast and collagen. Tea-tree has anti-inflammatory and antibacterial properties that can support the wound healing process. Objective: This study aims to determine the effect of tea tree get application on the number of blood vessel cells, fibroblasts, and collagen in post-exodontic sockets of male wistar rats. Research Methods: This study use a true experimental laboratories design with a post test - only control group design with a sample of 27 male Wistar rats which were divided into 9 groups, each group of which had 3 male Wistar rats and then added a reserve of 1 head of each group so the total sample and the reserve amounted to 36 heads. Exodontics were performed on the maxillary left central incisor to facilitate field view and reduce the risk of rat death. The concentration of tea tree gel used was 5%. The number of blood vessel cells, fibroblast and collagen density were observed and counted on days 3, 5 and 7 then the average was taken. Result: the result showed that the mean number of fibroblast cells, blood vessels and collagen density increased from day 3,5 and 7. Conclusion: it can be shown that the application of tea tree gel can increase fibroblast cells, blood vessels and collagen density in post-exodontic socket of male Wistar rats, thus accelerating the wound healing process.